1994
DOI: 10.1530/jrf.0.1010697
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cumulus expansion and nuclear maturation during bovine oocyte maturation in vitro by the addition of epidermal growth factor and insulin-like growth factor I

Abstract: This study was carried out to identify the possible effects of epidermal growth factor (EGF) and insulin-like growth factor-I (IGF-I) on cumulus expansion and nuclear maturation in bovine oocytes matured in vitro in serum-free media. Bovine follicular oocytes were matured in vitro and were then classified as cumulus cell-enclosed oocytes or denuded oocytes. They were then cultured for 24 h in TCM-199 (tissue culture medium-199) with EGF (50 ng ml-1), IGF-I (100 ng ml-1) and EGF plus IGF-I (50 and 100 ng ml-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
117
2
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 16 publications
16
117
2
3
Order By: Relevance
“…Chromatin was stained with 10 mg/ml propidium iodide for 5 min. After staining, oocytes were washed and mounted between a coverslip and a glass slide supported by silicone (Lorenzo et al, 1994) with antifade mounting medium (Vectashield; Vector Labs, Inc.), and the coverslip was sealed with nail polish. Samples were examined using laser-scanning confocal microscopy.…”
Section: Gene Expression In Cumulus-granulosa Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin was stained with 10 mg/ml propidium iodide for 5 min. After staining, oocytes were washed and mounted between a coverslip and a glass slide supported by silicone (Lorenzo et al, 1994) with antifade mounting medium (Vectashield; Vector Labs, Inc.), and the coverslip was sealed with nail polish. Samples were examined using laser-scanning confocal microscopy.…”
Section: Gene Expression In Cumulus-granulosa Cellsmentioning
confidence: 99%
“…Transcripts for IGF-I receptor were noted in the bovine oocyte (Yoshida et al, 1998;Yaseen et al, 2001). Accordingly, the presence of ligand was beneficial to IVM both in cumulus enclosed (Harper and Brackett, 1992;Lorenzo et al, 1994;Pawshe et al, 1998;Sirotkin et al, 1998) and in denuded bovine oocytes (Pawshe et al, 1998;Sirotkin et al, 1998). This suggests that the effect of IGF-I is not necessarily mediated by secretions of surrounding cumulus cells, although IGF-I increases responsiveness of granulosa cells to FSH (Monget and Bondy, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a significant difference between the rate of cumulus-intact oocytes matured with PMSG (89.5%) and without PMSG (45.9%) as shown in Table 2. Finally, EGF, which can induce cumulus-expansion except gonadotrophins [20], had the same effects as gonadotrophins on fertilizability of oocytes (Fig. 3).…”
Section: Resultsmentioning
confidence: 77%
“…The addition of gonadotrophin or epidermal growth factor (EGF) into maturation medium can enhance the cumulus-expansion [16,20]. Therefore, we examined the effect of the addition of these cumulus-expansion induced substance into maturation medium on the fertilizability of the oocyte.…”
mentioning
confidence: 99%
“…Both IGF-1R and IR are also present in the bovine oocytes and embryos (Nuttinck et al, 2004). Several studies have observed that COCs treated with IGF-I, alone or in combination with either epidermal growth factor or angiotensin II, showed increased cumulus expansion, improved rates of nuclear maturation and enhanced metabolism of pyruvate (Lorenzo et al, 1994;Stefanello et al, 2006). The intra-ovarian administration of IGF-I was able to improve the developmental capacity of oocytes from pre-pubertal cattle (Oropeza et al, 2004).…”
Section: Metabolic Hormonesmentioning
confidence: 99%